2013
DOI: 10.1016/j.molonc.2013.02.016
|View full text |Cite
|
Sign up to set email alerts
|

High expression of microRNA‐625‐3p is associated with poor response to first‐line oxaliplatin based treatment of metastatic colorectal cancer

Abstract: The backbone of current cytotoxic treatment of metastatic colorectal cancer (mCRC) consists of a fluoropyrimidine together with either oxaliplatin (XELOX/FOLFOX) or irinotecan (XELIRI/FOLFIRI). With an overall objective response rate of approximately 50% for either treatment combination, a major unsolved problem is that no predictors of response to these treatments are available. To address this issue, we profiled 742 microRNAs in laser-capture microdissected cancer cells from responding and non-responding pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
71
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 44 publications
6
71
0
Order By: Relevance
“…14) Several in vitro studies showed that L-OHP resistance is linked to the expression of miRNAs, such as miR-27b, miR-143, miR-181b, miR-203, and miR-1915. [15][16][17][18] Furthermore, the responses of patients with CRC to L-OHPbased chemotherapy have been associated with the up-regulated expression of miR-148a, miR-181b, and miR-625-3p. 17,19) However, these miRNAs may not be directly linked to EMT caused by the acquisition of L-OHP resistance in CRC cells because they have no binding sites to the 3′-untranslated region of ZEB1.…”
mentioning
confidence: 99%
“…14) Several in vitro studies showed that L-OHP resistance is linked to the expression of miRNAs, such as miR-27b, miR-143, miR-181b, miR-203, and miR-1915. [15][16][17][18] Furthermore, the responses of patients with CRC to L-OHPbased chemotherapy have been associated with the up-regulated expression of miR-148a, miR-181b, and miR-625-3p. 17,19) However, these miRNAs may not be directly linked to EMT caused by the acquisition of L-OHP resistance in CRC cells because they have no binding sites to the 3′-untranslated region of ZEB1.…”
mentioning
confidence: 99%
“…Further cohort study in 94 metastatic CRC patients treated first‐line with XELOX showed that high expression of miR‐625‐3p was confirmed to be associated with a poor clinical response. Their findings suggested that miR‐625‐3p may be a marker of responsiveness . Another study of the expression levels of 1,200 human miRNAs in colon cancer tissues, using laser capture microdissection and miRNA profiling arrays showed a low level of miR‐4299 expression and the high levels of miR‐196b expression are related to advance OS in colon cancer patients treated with XELOX .…”
Section: Micrornas Prediction Of Oxaliplatin Response and Crc Treatmentioning
confidence: 99%
“…Boisen et al reported that high expression of miR-196b-5p and miR-592 predicted improved prognosis of mCRC patients receiving XELOX therapy, while high miR-664-3p and low miR-455-5p levels were correlated with improved outcome under XELOX plus bevacizumab treatment [78]. By using laser capture microdissected cancer cells from responsive and non-responsive patients receiving XELOX/FOLFOX, Rasmussen et al found that high level of miR-625-3p was associated with poor response but was not associated with disease recurrence, indicating that miR-625-3p is solely a response biomarker for XELOX/FOLFOX treatment in mCRC patients [79].…”
Section: Mirna Biomarkers Of Clinical 5-fu/oxaliplatin Responsementioning
confidence: 99%